Kondisi Sosial-Ekonomi dan Alasan Bertahannya Masyarakat di Daerah Rawan Banjir di Kelurahan Hamdan Medan Maimun Kota Medan - Sirait, Firli Nur Afdilla; Luluk, Theresia Angeline; Halim, Jennifer Irene; Manik, Anggreny Br.; R, Rohani; Kardiana, Elsa (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study shows that people in Hamdan Village have diverse social responses in dealing with floods. For old residents, floods are not a big problem because they have become part of their daily lives, while newcomers tend to be more psychologically affected. Although floods often occur, people still try to anticipate their impacts, such as building houses with high foundations and helping each other when disasters occur. Floods actually strengthen social relations in the community through cooperation in evacuation, early warning, and post-flood mutual cooperation. Economically, people in Hamdan Village generally have low-skilled jobs, such as factory workers, small traders, or laundry workers. Floods disrupt several livelihoods, especially for those who work from home or depend on the conditions of the surrounding environment. However, government assistance and social organizations help maintain the economic stability of the community during floods. People’s decisions to remain in flood-prone areas are influenced by various factors, including emotional attachment to their family’s inherited residence, strong social ties with the surrounding environment, and economic limitations that make it difficult for them to move to a safer place. In addition, the strategic location of Hamdan Village is also the main reason they remain, especially because of easy access to the workplace and relatively affordable living costs.